Perancangan Sarana Display Produk Aksesoris Handmade untuk UMKM : Studi Kasus “Erve The Label” - Nabilah Hashifah; Maharani Permanasari (Penerbit Itenas, 2024)
Creative industries in Indonesia, especially UMKM engaged in handmade accessories, have great potential to grow. However, one of the challenges faced by UMKM is the limitation in displaying their products attractively. This final project research is a process of designing a display facility for handmade accessories products intended for UMKM exhibitions with a case study of Erve The Label. This is motivated by the desire of the owner of Erve The Label to have a display that is different from the others by prioritizing function and visuals. The design thinking research method that begins with observations and interviews with target users is expected to produce display facilities that are in accordance with the brand image. This design produces display facilities that are in accordance with the image of Erve The Label by utilizing the brand logo as a visual concept.